2023
DOI: 10.1186/s12879-023-08209-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and tolerability of antimicrobial agents for complicated intra-abdominal infection: a systematic review and network meta-analysis

Abstract: Background Which antimicrobial agents provide the optimal efficacy, safety, and tolerability for the empirical treatment of complicated intra-abdominal infection (cIAI) remains unclear but is paramount in the context of evolving antimicrobial resistance. Therefore, updated meta-analyses on this issue are warranted. Methods We systematically searched four major electronic databases from their inception through October 2022. Randomized controlled tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Though well studied for antibacterial activity against infections in adults, its safety and effectiveness in pediatrics have not been established. Moreover, dosage adjustment is warranted in patients with severe hepatic and/or renal impairment (Table 2) [57,58]. To some extent, resistance in some bacteria to eravacycline is associated with up-regulated, non-specific intrinsic MDR efflux, and target-site modifications, such as 16s rRNA or certain 30S ribosomal proteins [53].…”
Section: Eravacyclinementioning
confidence: 99%
See 1 more Smart Citation
“…Though well studied for antibacterial activity against infections in adults, its safety and effectiveness in pediatrics have not been established. Moreover, dosage adjustment is warranted in patients with severe hepatic and/or renal impairment (Table 2) [57,58]. To some extent, resistance in some bacteria to eravacycline is associated with up-regulated, non-specific intrinsic MDR efflux, and target-site modifications, such as 16s rRNA or certain 30S ribosomal proteins [53].…”
Section: Eravacyclinementioning
confidence: 99%
“…Recent clinical trials also demonstrated its use in pyelonephritis and cystitis. Though it has very less drug-drug interactions, it should be avoided with dairy and divalent cation-containing products for at least 4 h of duration after the dosing [52,56,58].…”
Section: Eravacyclinementioning
confidence: 99%